Evaluation of Transformer Protection System Coordination at ULTG Jeneponto - Basri, Nur Ahmad; Bakhtiar, Bakhtiar; Tahir, Muhammad; Asri, Andarini (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
Power transformers are essential components in electrical power systems as they transform electrical quantities. In practical terms, electrical power systems may experience disturbances such as short-circuit faults, either between phases or to ground. One type of relay used to accommodate these faults is the Over Current Relay (OCR) for phase-to-phase faults and the Ground Fault Relay (GFR) for ground faults. This research evaluates the coordination settings of transformer protection systems at PT PLN (Persero) ULTG Jeneponto by analyzing the characteristics plot of each transformer unit. The evaluation results reveal intersecting characteristics on the high voltage (HV) and medium voltage (MV) sides of Transformers #3 Tallasa and #3 Bulukumba. By implementing recommended settings for these two transformer units, anomalies can be addressed, and the protection system can coordinate effectively.